Cantonal Road Conservation Plans to Strengthen Municipal Action in Costa Rica - Campos Cruz, Carlos (2025)
Road management at the municipal governments in Costa Rica is a relatively new activity for local authorities, since the law No. 8114 in 2001, set up new responsibilities and dedicated funding for road maintenance.However, municipal road management has been practiced by traditional policies, criteria and practices of road management in the national highway system.LanammeUCR started given technical support to municipal governments a few years ago, mainly, from 2007, this institution tried to establish cooperation agreements with municipalities to provide them with technical assistance and training to improve their road management activities. The goals of the technical assistance are aimed to change the empirical practice and create modern road management systems to produce better transportation service for the communities and regions.This article describes some of the work performed by the depariment of technical assistance to municipalities in LanammeUCR thru the cooperation agreement that are currently signed with 15 municipalities in Costa Rica. It deals with the main activities for doing a technical condition survey of the municipal roads and the efforts to write a five year road maintenance plan for local governments. It also presents some management indicators that could be used to analyze the improvements in road management results at the municipal governments.